Conceptions of the border and behaviors of cross-border actors - Belkacem, Rachid; Boquet, Mathias; Dorkel, Nicolas; Renard-Grandmontagne, Colette; Siadou-Martin, Béatrice; Yildiz, Hélène (Projectics / Proyéctica / Projectique, 2022)
Abstract: „Based on the example of the Grande Région (Greater Region), this research note retains a systemic approach to the cross-border area and focuses on trade and consumption in this territory. It defines this space as a trade system in a border zone made up of actors (national and/or foreign distributors, consumers), places (sales outlets of varying size) registered in a territory, and practices (consumption practices, implementation strategies) that are in interaction. Four points are discussed. First, distance to the border is questioned, leading us to compare actors’ perceptions with the actual distance. Second, we examine the links between work, mobility, and consumption. The third section focuses on individuals as consumers and underlines the importance of psychological, sociological, and cultural variables. Finally, a focus on retailer strategies underlines the need to take into account specificities for the implementation of commercial strategies. This research note invites us to conduct further research on trade in the cross-border space by outlining the framework of a research agenda.“
Keywords: Grenzarbeitnehmer; Handel; Verbrauch

Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch